Relevansi Konsep Pendidikan Multikultural Berbasis Pendekatan Ki Hadjar Dewantara terhadap Pendidikan Islam di Indonesia - Khafifatul Fian; Muhammad Hananika Anugerah Yusuf (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2021)
This article aims to discuss the relevance of multicultural education based on the Ki Hadjar Dewantara approach and Islamic learning in Indonesia. This research is a library research with the process of collecting data based on documents both books and journals as well as analyzing data using analytical methods and presented descriptively. The author analyzes, describes, and summarizes some of the data collected. The result showed that multicultural education is an education aimed to develop the skills of the learner. Multicultural education is a tool to prevent discrimination to create a mutual respect between teacher and student, between teacher and teacher, and student and student. In the Islamic education, the concept of skill development is based on the Quran and Hadis. In Islamic view, education is expected to provide the direction learner’s growth or development.